2013
DOI: 10.1037/a0029982
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of approach-alcohol action tendencies, working memory capacity, and current task goals predicts the inability to regulate drinking behavior.

Abstract: The inability to regulate alcohol consumption has been attributed to an imbalance between stimulus-driven behavioral biases, or action tendencies, and the ability to exert goal-directed control, or working memory capacity (WMC). Previous research assessing the interaction between these variables has not considered the effect of whether individuals' current goals or task demands require goal-directed control. Our aim was to examine the potential interaction of appetitive action tendencies and the ability to exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 85 publications
(108 reference statements)
3
34
0
Order By: Relevance
“…This is in line with a central tenet of Wiers et al's (2007) model, namely that with limited capacity to self-regulate, impulsive processes influence behavior. This finding aligns with some previous research (Ostafin et al, 2008;Salemink & Wiers, 2014;Sharbanee et al, 2013;van Hemel-Ruiter et al, 2015), which found that impulsive alcohol-related cognitive processes predicted alcohol use when working memory/executive control capacity was low.…”
Section: Discussionsupporting
confidence: 81%
“…This is in line with a central tenet of Wiers et al's (2007) model, namely that with limited capacity to self-regulate, impulsive processes influence behavior. This finding aligns with some previous research (Ostafin et al, 2008;Salemink & Wiers, 2014;Sharbanee et al, 2013;van Hemel-Ruiter et al, 2015), which found that impulsive alcohol-related cognitive processes predicted alcohol use when working memory/executive control capacity was low.…”
Section: Discussionsupporting
confidence: 81%
“…This contrasts with alternate methodologies [16,33], and may suggest that the SA/ATT is less susceptible to WM confounds.…”
Section: Discussionmentioning
confidence: 98%
“…[16,[28][29][30][31] Selective-attention and action-tendency assessment trials. In the selective-attention assessment trials, attention is secured by requiring participants to identify lines as matching or non-matching (subfigures a, c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in spider anxious individuals, the sight of a spider may directly activate an avoidance tendency, while the explicit belief that spiders are terrifying may also lead to the behavioral decision to avoid rather than to approach the spider. Therefore, future research may use an explicit measure that can reveal a response conflict between the two systems (Sharbanee et al, 2013), such as a measure that captures participants' whish or motivation to overcome their spider fear for instance in treatment-seeking individuals.…”
Section: Discussionmentioning
confidence: 99%